137k views
5 votes
Rearrange the formula F = mg + ma for a.

A) a = Fm - g
B) a=m/F+g
C) a=m/F-g
D) a= F/m-g

User MKay
by
5.3k points

2 Answers

6 votes

Ok work is shown below:


F = mg + ma

-ma + F = mg

-ma = mg - F

-a = g - F/m

a = F/m - g


Hope this helps you out!

User Eyn
by
4.5k points
2 votes
ANSWER

The correct answer is option D.


a = (F)/(m)-g



EXPLANATION

The given formula is



F = mg + ma


We want to solve this formula for a, so we add


- mg

to both sides of the equation to get,



F - mg=ma


We now divide through by m, to obtain,


(F)/(m) - (mg)/(m) = (ma)/(m)


Let us cancel out the common factors to get,


(F)/(m) - g =a

We can also rewrite this to obtain,


a = (F)/(m)-g
Therefore the correct answer is D.

User Krzysztof Madejski
by
5.6k points